(untitled) (Global Journal of Science Frontier Research, 2026)
This paper proposes the Principles of Matter or Laws of Unity as a unified framework for understanding gravity, inertia, and the formation of physical structures across all scales. In this model, matter organises into hierarchical unities through two intrinsic forms of energy: sharing-energy (Es) and excess-energy (Ee). Together they cause the generalised inertia or unity force (Fu = Es + Ee), in which Es causes an active and constant pull toward a unity centre as inertia-at-rest or gravity or weight, and Ee produces inertia-in-motion or heat. This approach challenges the foundations of relativity by asserting that matter moves only relative to its unity centre. The paper applies the Principles of Matter to atomic structure, electricity, photonic behaviour, nuclear fusion, planetary motion, and galactic organisation, arguing that unity force or inertia is the single fundamental force underlying all natural forces. The model further explains galaxies as ultimate unities centred on black holes in which potential-energy fully converts to sharing-energy, producing infinite pull. A measurement method-the Breaking-point Excess-energy Method-is proposed to quantify inertia-at-rest (gravity) based on the minimum energy required to break a unity, with an optional empirical mass-distance equation for estimation. Overall, the Principles of Matter provide a cohesive reinterpretation of natural forces, energy transfer, and cosmic structure formation.